(untitled) (Journal of Informatics Education and Research, 2023)
The Covid-19 pandemic has accelerated the adoption of information and communication technology (ICT) across primary, secondary and higher education levels in India. This article examines the relationship between assistant professors’ innovative learning and digital transformation in education. The study uses Google Forms to collect survey data from 210 college professors using convenience sampling, ensuring representation across gender, educational levels, and years of experience. The findings reveal significant variations in respondents’ perceptions of Digital Transformation, Service Quality and Digital Competence based on their educational levels. Post hoc tests further elucidate the nuanced differences among educational levels and years of experience. The analysis reveals the pivotal role of digital transformation in shaping perceptions and experiences in higher education. This research contributes valuable insights into the evolving landscape of digital education, shedding light on the dynamic interplay between educational levels, experiences, and key variables in the realm of digital transformation.